Emotional Intelligence on Career Adaptability: The Mediating Role of Career Decision Self Efficacy of Final Year Students - Hidayah, Farras Rahmat; Zona, Mega Asri (Human Resource Management Studies, 2024)
Purpose - This study aims to examine: (1) the effect of emotional intelligence on career adaptability (2) the effect of emotional intelligence on career adaptability (3) the effect of career decision self efficacy on career adaptability (4) the effect of emotional intelligence on career adaptability through career decision self efficacy among college students. Methodology - This research is a causal research. The population of this study were final year students of the Faculty of Economics and Business, Padang State University. The number of samples used was a population of 100 students who were taken using total sampling. Data collection using a questionnaire with a Likert Scale. The analysis technique used through SmartPLS 4 software. Results - The results of data processing in this study indicate that: (1) emotional intelligence has a positive and significant effect on career adaptability in FEB UNP final year students (2) emotional intelligence has a positive and significant effect on career decision self efficacy in FEB UNP final year students (3) career decision self efficacy has a positive and significant effect on career adaptability in FEB UNP final year students (4) career decision self efficacy mediates the effect of emotional intelligence on career adaptability in FEB UNP final year students.